1019 SAFETY OF PLUG-BASED AND SUTURE-BASED VASCULAR CLOSURE DEVICES IN PATIENTS UNDERGOING TRANSCATHETER AORTIC VALVE REPLACEMENT: A MULTICENTER OBSERVATIONAL STUDY. (15th December 2022) - Panarello, Alessandra; Sorrentino, Sabato; Franzone, Anna; Bruno, Federica; Sportelli, Martina; Carabetta, Nicole; Di Costanzo, Assunta; Polimeni, Alberto; Angellotti, Domenico; Castiello, Domenico Simone; Simonetti, Fiorenzo; Spaccarotella, Carmen; et al.
Abstract: Background: Transcatheter aortic valve replacement (TAVR), is the treatment of choice for most patients with aortic stenosis. Transfemoral access remains the most widely used peripheral vascular approach for TAVR and dedicated plug-based or suture-based vascular closure devices are available to achieve femoral hemostasis. However, the comparative safety of such strategies is controversial in patients undergoing transfemoral TAVR. Objectives: in this study, we aimed to evaluate the rates of vascular access complications according to the use of plug-based or suture-based vascular closure in patients undergoing TAVR. Methods: Data were retrospectively collected from two high-volume TAVR centers from September 2009 to March 2022. Patients were categorized according to the use of plug-based or suture-based vascular closure devices. The plug-based platform used was MANTA (Teleflex), while the suture-based devices were the Perclose ProGlide™ or the Prostar™ Systems (Abbott Vascular). Baseline demographic, clinical, and echocardiographic variables were compared between these groups using an independent-sample Student's t-test for continuous variables, presented as mean±SD, and the chi-square test for categorical or binary variables, presented as number and percentage, as appropriate. The odds ratio (OR) for vascular complications was calculated using a multivariate logistic regression model including as dependent variables all relevant baseline and procedural characteristics. The closure device variable was included in the multivariate model using the Prostar™ XL device group as reference. Vascular complications were adjudicated according to the Valve Academic Research Consortium definitions 3. Results: Out of 874 patients, hemostasis was achieved with Prostar™ XL PVS in 120 (13.7%) patients, with Perclose ProGlide™ in 525 (60.1%), and with MANTA 229 (26.2%). No differences in age and common cardiovascular risk factors were observed between the group except for the prevalence of peripheral arterial disease (30.6% vs. 17.0%, p<0.0001) and dyslipidemia (58.9% vs. 68.6%, p=0.01) as well as for the echo and procedural variables except for the Euroscore II that was lower in the plug-based group (6.0±5.6 vs. 5.1±4.68), and for the higher use of new generation devices (79.1% vs. 98.3%, p<0.0001). After adjustment for common cardiovascular risk factors and procedural features, no differences were observed for total vascular complications [OR: 0.68 (95% confidence interval (CI): 0.33 to 1.38) and OR: 0.60 (95% CI: 0.33 to 1.53), for Perclose ProGlide™ and MANTA groups, respectively]. Likewise, no substantial differences were observed for major and minor vascular complications. Conclusions: Both suture-based and plug-based devices have comparable outcomes with regard to the risk of vascular complications. Further randomized clinical trials are warranted to confirm this observation in high-risk sub-group patients with for example heavily calcified access or obesity.